2016
DOI: 10.1093/ejcts/ezw107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes between neuroendocrine thymic tumours and other subtypes of thymic carcinomas: a joint analysis of the European Society of Thoracic Surgeons and the International Thymic Malignancy Interest Group

Abstract: This represents the largest clinical series of TCs and NETTs collected. Despite the biological aggressiveness of these rare neoplasms, the 5-year survival rate after resection is over 60% and TCs and NETT showed a similar rate of survival and recurrences after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 20 publications
4
40
0
Order By: Relevance
“…Similar to published reports, we found that TNETs were larger than thymomas and thymic carcinomas, but were not significantly different ( P = 0.15) . Moreover, compared to other thymic tumors, TNETs were more likely to present with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to published reports, we found that TNETs were larger than thymomas and thymic carcinomas, but were not significantly different ( P = 0.15) . Moreover, compared to other thymic tumors, TNETs were more likely to present with lymph node metastasis.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to published reports, we found that TNETs were larger than thymomas and thymic carcinomas, but were not significantly different (P = 0.15). 6,27 Moreover, compared to other thymic tumors, TNETs were more likely to present with lymph node metastasis. Weksler et al analyzed thymic carcinoma and TNET patients who underwent lymph node dissection and suggested that nodal metastases may be a negative prognostic factor in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete surgical resection with or without chemotherapy seems to have a better outcome [9, 17]. The therapeutic modalities used in thymic NET are often those of lung NET; however, specific treatment for thymic tumors needs to be clearly defined [5, 17].…”
Section: Discussionmentioning
confidence: 99%
“…The interest on surgical management of thymic neoplasms has never been so evident as in the last few years, following the publication of several multi-institutional large series, especially thanks to a formidable scientific effort by the European Society for Thoracic Surgeons (ESTS) and the International Thymic Malignancy Interest Group (ITMIG) (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%